A program and project management approach for collaborative university-industry R&D funded contracts - Fernandes, Aldora Gabriela Gomes (2015)
This paper presents a new program and project management (PPM) approach especially devoted to support collaborative university-industry R&D funded contracts. While the literature provides some advice on how to embark on designing such PPM approach, university-industry collaboration contexts require specific guidance. The research described in this paper aims to make some contribution to theory as well as to practice by discussing the PPM approach adoption in a case study collaborative university-industry R&D funded contract between the University of Minho and Bosch Car Multimedia Portugal S. A., named - HMIExcel. The results show that emphasis should be given to structured objective setting, good progress monitoring and effective communication. The research study is ongoing through the use of a questionnaire and focus groups, in order to improve the presented PPM approach conceptualization.